Evaluation of English Program Using Model of Countenance Stake in University of East Kalimantan - Widya Noviana Noor; Rostanti Toba; Hafi Nanda (Southeast Asian Journal of Islamic Education, 2019)
The research aims to evaluate English Department by using model of Countenance Stake on the components of context, input, process, and product. The research is an evaluation research. The research done in four universities, they are IAIN Samarinda, ABA Colorado Balikpapan, Universitas Kutai Kartanegara and Universitas Muhammadiyah Kalimantan Timur. The data is collected by observation, interview, and documentation, and then analyzed in a qualitative descriptive way. The result of the research on the aspect of Antecedents shows that English Department is not yet in line with the institution’s stand, that is the department’s vision, mission and goals that have been compiled; Transaction, in the evaluation of input, the factors that affect the learning process, such as learning media, they are syllabus, SAP, test, and strategy in learning made by the lecturer of the English Department is good and the outcome of product includes the students learning outcome in one semester is good which is in accordance with the achievement that the department wants to achieve.